Feed efficiency improvement and aquaculture waste conversion to economically valuable product - Harris, Enang (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
Fish farmer cannot reduce feed price, however they can reduce feed cost for fish producing. Feed cost is highly determined by feeding rate (FR); whether in maximum FR or restricted FR, and dissolved oxygen level in water. The present paper reviews a detail explanation concerning both factors on feed efficiency. Amongst other water quality parameters, oxygen is the most important factor and therefore must be closely monitored. Moreover, dissolved oxygen cannot be detected only by visual observation. Biofloc technology and PAS (partitioned aquaculture system) can change waste into bacteria and phytoplankton biomass which can be further utilized as fish feed. The major difference between these systems is in the oxygen requirement. This paper also presents some experiment results and preliminary applications in field scale that have been performed in Indonesia.Keywords: feeding rate, oxygen, feed efficiency. ABSTRAKPembudidaya ikan tidak bisa menurunkan harga pakan, tetapi dapat menurunkan biaya pakan untuk memproduksi ikan. Biaya pakan sangat ditentukan oleh feeding rate (FR); apakah ”maksimum FR” atau ”restricted FR”, dan oksigen terlarut dalam air. Dalam artikel ini diuraikan secara rinci mengenai pengaruh kedua faktor tersebut terhadap efisiensi pakan. Oksigen merupakan faktor yang paling penting di antara kualitas air, oleh karena itu kadar oksigen terlarut harus diukur. Oksigen terlarut tidak dapat dideteksi dengan panca indera manusia. Teknologi biofloc dan PAS (partitioned aquaculture system) mampu mengubah limbah jadi bakteri dan fitoplankton yang siap untuk menjadi makanan ikan. Perbedaannya antara kedua sistem terletak pada kebutuhan oksigen. Artikel ini juga memuat hasil percobaan dan praktik rintisan skala lapangan yang telah dilaksanakan di Indonesia.Kata kunci: feeding rate, oksigen, efisiensi pakan.